The Influence of Social Commerce Construct on Consumer Trust and Purchase Intention at Shopee Indonesia - Al-Jundi, Rega Dinzki; Ardansyah, Ardansyah (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this research is to find out how big social commerce construct on consumer trust in Shopee Indonesia and to find out how much influence it has social commerce construct on purchase intentions at Shopee Indonesia. This research uses quantitative methods with a sample size of 100 respondents from social commerce Shopee Indonesia data in this research was analyzed using SPSS Version 25.0 analysis assistance. The research results show that social commerce construct has a significant positive effect on consumer trust in Shopee Indonesia as well social commerce construct has a significant positive effect on purchase intention at Shopee Indonesia.